Analisa Sistem Akuntansi Penggajian Sebagai Upaya Peningkatan Efektivitas Pengendalian Internal di Wisata Lon Malang - Izzatul Aini; Muhammad Asim Asy'ari (CV. Ulil Albab Corp, 2024)
The accounting system is a crucial tool for controlling a business and preventing potentially harmful situations. In an attempt to improve internal control efficacy, this study examines Lon Malang Beach Tourism's payroll accounting system. In order to minimize errors and fraud, it is hoped that Lon Malang tourism managers will take this research into mind and utilize its input to formulate strategies for implementing a payroll accounting system. Using a case study methodology, this research is qualitative in nature. Primary and secondary data are the two types of data that are employed. Techniques for gathering data include observation, interviewing, and documentation. The study's findings indicate that Lon Malang Tourism's payroll accounting system is effective, yet not entirely effective due to multiple missing papers and functional duplication